POLITIK IDENTITAS DALAM PERSPEKTIF ALQUR’AN DAN HADITS - Efendi, Indra; Charles, Charles (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
his study uses a qualitative approach, namely to describe and elaborate on educational methods from the perspective of the Koran and hadith. The data collection technique used in this research is library research (Library Research) where library research is the activity of collecting materials related to research originating from the Al-Qur'an, Hadith, books, scientific journals, literature and other publications that are worthy of being used as sources for research that will be examined by the author. The results of the study show that educational methods in the perspective of the Koran are: Requirements for leaders in Islam: 1) Islam, 2) Men, 3) Taklif, 4) Knowledge, 5) Fair, 6) Ability and skills, and 7) Physically healthy and spiritual. The concepts of leadership in the hadith of the Prophet saw are: (1) leadership is a must, (2) obedience to the leader is an obligation with the exception if the leader orders to commit immorality, (3) there can only be one leader because if there are more than that , the potential for division and cross-policy is very large, (4) the leader must be appointed by the people, (5) self-reliant as a leader is unethical, (6) the leader must be from among men.